The art of the ‘common good’: Property and nature values in strategic land-use planning in Finland - Salo, Matti; Puustinen, Sari; Jounela, Pekka; Hänninen, Harri; Hiedanpää, Juha (Elsevier, 2025)
Cutting across many biophysical, institutional, cultural, and psychological boundaries, the quest for the ‘common good’ is an enduring legitimation for land-use planning interventions that go beyond statutory planning, even supporting the emergence of new commons. We analyse a body of qualitative and semi-quantitative data from a recent strategic land-use plan process in Southwest Finland, including a series of planning documents and the results of a Q study. We describe how planners, citizens, and stakeholder organisations co-created a regional land-use plan and, focusing on the relationships between the practice of land-use planning and the legal structures of private property, ask how the commons were advanced in relation to private land ownership and how the different interpretations of the common good were reflected in the process. In the studied process, the planners strove to emphasise the commons and the common good by introducing new strategic land-use symbols.
However, the emergence of new commons was seen as a threat by many landowners, their advocacy organisations, and regional decision makers. Instead of an unavoidable impasse, we urge that the situation should be seen as a call for novel solutions in the face of the ambitious and spatially explicit nature conservation commitments that increasingly contest the prevailing perceptions of the relationships of nature, property, and the distinct interpretations of common good.